Empirical porewater pressure generation model parameters in 1-D seismic site response analysis. Issue 114 (November 2018) - Mei, Xuan; Olson, Scott M.; Hashash, Youssef M.A.
Abstract: The Vucetic-Dobry porewater pressure (PWP) generation model is implemented in widely used one-dimensional site response analysis software. This PWP model relates excess PWP ratio, shear strain amplitude and number of cycles, and requires only three curve-fitting parameters from undrained cyclic shear tests. In this study, new empirical correlations were developed and validated using different databases of undrained cyclic direct simple shear and triaxial tests on a number of clean, subangular to subrounded, silica sands to relate model parameters to relative density (Dr ) and uniformity coefficient (CU ). These correlations permit PWP estimates without advanced laboratory testing, yet exhibit small values of mean residual and standard deviation, and illustrate the importance of CU on PWP generation. Highlights: D﻿e﻿v﻿e﻿l﻿o﻿p﻿e﻿d﻿ ﻿r﻿e﻿l﻿a﻿t﻿i﻿o﻿n﻿s﻿ ﻿f﻿o﻿r﻿ ﻿V﻿u﻿c﻿e﻿t﻿i﻿c﻿-﻿D﻿o﻿b﻿r﻿y﻿ ﻿P﻿W﻿P﻿ ﻿m﻿o﻿d﻿e﻿l﻿ ﻿f﻿o﻿r﻿ ﻿u﻿s﻿e﻿ ﻿i﻿n﻿ ﻿1﻿D﻿ ﻿s﻿i﻿t﻿e﻿ ﻿r﻿e﻿s﻿p﻿o﻿n﻿se﻿ ﻿a﻿n﻿a﻿l﻿y﻿s﻿i﻿s. ﻿PW﻿P﻿ ﻿m﻿o﻿d﻿e﻿l﻿ ﻿p﻿a﻿r﻿a﻿m﻿e﻿t﻿e﻿r﻿s﻿ ﻿a﻿r﻿e﻿ ﻿f﻿u﻿n﻿c﻿t﻿i﻿o﻿n﻿s﻿ ﻿o﻿f﻿ ﻿r﻿e﻿l﻿a﻿t﻿i﻿v﻿e﻿ ﻿d﻿e﻿n﻿s﻿i﻿t﻿y﻿ ﻿a﻿n﻿d﻿ ﻿g﻿r﻿a﻿i﻿n﻿ ﻿s﻿i﻿z﻿e﻿ ﻿d﻿i﻿s﻿t﻿r﻿i﻿b﻿u﻿t﻿i﻿o﻿n. C﻿o﻿m﻿p﻿u﻿t﻿e﻿d﻿ ﻿P﻿W﻿P﻿ ﻿f﻿o﻿r﻿ ﻿c﻿l﻿e﻿a﻿n﻿ ﻿s﻿a﻿n﻿d﻿s﻿ ﻿y﻿i﻿e﻿l﻿d﻿s﻿ ﻿s﻿m﻿a﻿l﻿l﻿ ﻿r﻿e﻿s﻿i﻿d﻿u﻿a﻿l﻿s﻿ ﻿a﻿n﻿d﻿ ﻿s﻿t﻿a﻿n﻿d﻿a﻿r﻿d﻿ ﻿d﻿e﻿v﻿i﻿a﻿t﻿i﻿o﻿n.